Perceptions, Barriers, and Real-Life Impact of Communication Skills Training among Pharmacy Students: A Cross-Sectional Study - Samineni, Neeraja Rani; Mandava, Kiranmai (Indian Journal of Pharmacy Practice)
Objectives: To explore the perceptions of pharmacy students and faculty toward communication skills training, identify the barriers that hinder its development, and examine how a lack of communication skills affects real-life academic and professional scenarios. This objective aims to shed light on how communication is valued within pharmacy education, how students and faculty perceive its relevance in clinical and academic settings, and why it often remains underemphasized despite its importance. It also seeks to uncover specific challenges such as curriculum limitations, lack of practical exposure, language issues, and limited assessment methods that prevent students from acquiring these vital skills. Furthermore, it investigates the broader consequences of poor communication, including misunderstandings during patient interactions, reduced academic performance, hindered teamwork, and missed career opportunities-emphasizing the urgent need for structured communication training in pharmacy programs. Materials and Methods: A mixed-methods cross-sectional study was conducted among 1000 pharmacy students and 100 faculty members across multiple institutions. Data were collected through structured questionnaires, focus group discussions, and classroom observations. Quantitative data were analyzed using descriptive statistics and correlation tests, while qualitative insights were drawn from thematic analysis. Results: The majority of students acknowledged the importance of communication in theory but prioritized technical subjects in practice. Barriers such as public speaking anxiety, language challenges, and limited exposure to real-life counseling scenarios were reported. A statistically significant correlation (r = 0.71, p < 0.05) was found between communication training and leadership confidence. Additionally, students with poor communication skills reported difficulties in viva exams, presentations, internships, and patient interactions. Faculty echoed these concerns, highlighting the urgent need for integrated training programs. Conclusion: Communication skills are not an optional soft skill but a critical professional competency. Pharmacy students must be exposed to structured and engaging communication modules to enhance academic performance, confidence, and employability.
Keywords: Communication Skills; Pharmacy Education; Soft Skills; Student Perception; Mixed-Methods Research; Focus Group Discussion; Healthcare Communication; Patient Counseling; Curriculum Reform